The Morbidity of Reoperative Surgery for Recurrent Benign Nodular Goitre: Impact of Previous Unilateral Thyroid Lobectomy versus Subtotal Thyroidectomy. (19th January 2014) - Rudolph, Navin; Dominguez, Claudia; Beaulieu, Anthony; De Wailly, Pierre; Kraimps, Jean-Louis
Abstract : Background . Subtotal thyroidectomy (STT) was previously considered the gold standard in the surgical management of multinodular goitre despite its propensity for recurrence. Our aim was to assess whether prior STT or unilateral lobectomy was associated with increased reoperative morbidity. Methods . A retrospective analysis was conducted extracting data from our endocrine surgical database for the period from January 1991 to June 2006. Two patient groups were defined: Group 1 consisted of patients with previous unilateral thyroid lobectomy; Group 2 had undergone previous STT. Specific outcomes investigated were transient and permanent recurrent laryngeal nerve (RLN) injury and hypoparathyroidism. Results . 494 reoperative cases were performed which consisted of 259 patients with previous unilateral lobectomy (Group 1) and 235 patients with previous subtotal thyroidectomy (Group 2). A statistically significant increase relating to previous STT was demonstrated in both permanent RLN injury (0.77% versus 3.4%, RR 4.38, P = 0.038 ) and permanent hypoparathyroidism (1.5% versus 5.1%, RR 3.14, P = 0.041 ). Transient nerve injury and hypocalcaemia incidence was comparable. Conclusions . Reoperative surgery following subtotal thyroidectomy is associated with a significantly increased risk of permanent recurrent laryngeal nerve injury and hypoparathyroidism when compared with previous unilateral thyroidectomy. Subtotal thyroidectomy should therefore no longer be recommended in the management of multinodular goitre.